Pengaruh Volume, Lama Pendiaman dan Suhu Penyimpanan Darah Pada Pemeriksaan Mikrohematokrit Terhadap Nilai Hematokrit - Anik Nuryati; Suhardjono Suhardjono (POLTEKKES KEMENKES YOGYAKARTA, 2016)
Hematocrit is a special blood test to help diagnose a variety of diseases, including Dengue Hemorrhagic Fever (DHF), anemia, and polycythemia. Several obstacles often encountered in the examination, such as blood sampling volume, a delay time of inspection, and storage temperature. This study aims to determine the effect of high-volume variation, the standing time and the storage temperature of blood for hematocrit values. Thus it can provide information for health care workers and laboratory technician to determine a better microhematocrit examination. The type of the research is Quasi-Experiment since there is no randomization. The research was conducted from May to October 2015 in Yogyakarta Regional Health Laboratory and Citra Pratama Laboratory. The subjects were 10 men, aged 20-50 years, healthy (regular blood checks). Venous blood was taken as much as 5 ml and divided into 5 bottles of vials contained EDTA anticoagulant. One bottle was checked immediately; four bottles were stored for 1 and 2 hours at room temperature (16°C) and refrigerator temperature (8°C). The blood was inserted into 3, 4, 5, and 6 cms microhematocrit tube. The tip of the tube was closed by wax and then centrifuged 15,000 rpm for 5 minutes. The number of tightly-packed erythrocytes was read with haematocrit scale. The examination result showed that the hematocrit score was stable at 4 cms blood volume height, and was stored at 8°C temperature for an hour and at 16°C temperature for 2 hours. Hematocrit blood samples still showed normal range in the variations of blood volume height of 3, 4, 5 and 6 cm, withstanding time of 1 and 2 hours, and the temperature of 8°C and 16°C. There was no effect of volume height, standing time and blood storage temperature on hematocrit scores. It can be concluded that hematocrit score is stable at 4 cms blood volume height, 8°C storage temperature for an hour and at room temperature for 2 hours. There is no effect of volume, standing time and blood storage temperature on hematocrit scores.